Magnetotransport studies of heterostructures based on transition metals and their oxides - Huang, Ke (Nanyang Technological University, 2021)
To contribute to the next-generation electronic and spintronic devices, systematic investigations on emerging magnetotransport phenomena are in demand. Among the various condensed matter systems which might nurture these phenomena, the heterostructures based on the transition elements are intriguing. This thesis includes studies of three representative systems, namely (i) transition metal nanostructures, (ii) transition metal oxide heterostructures, and (iii) transition metal oxide superlattices. This thesis focuses on discovering novel longitudinal and transverse magnetoresistance at transition metal (oxides) based heterointerfaces and revealing their underlying charge transport mechanisms. In the first system, we propose and demonstrate that the spin textures in synthetic antiferromagnetic Pt/Co-based nanostructure are controllable via structural engineering. Primarily through modulating the thickness of the bottom layers in the nanostructure, the transition from skyrmion bubble to antiferromagnetic or ferromagnetic spin textures could be artificially switched. More importantly, the nano-engineered structure arouses an asynchronous annihilation of skyrmion bubbles. By utilizing this asynchronicity, we realized multiple non-volatile resistance states. In the second system, we achieve the modulation of charge carriers in TiOxDy/SrTiO3 heterostructures from electron to bipolar (electron and hole) conduction. The heterostructures are fabricated by treating Ti film with deuterium (D) doping and surface/interface oxidation. The electron mobility of the D-doped sample is 10 times as large as that of the undoped one. More importantly, the emerging holes exhibit high mobility comparable to that of the electrons. Furthermore, we also observe a giant magnetoresistance (MR), more than 900% at 6 T, which intrinsically is induced by this bipolar conduction. In the last system, we report the modulation of the strength and symmetry of the magnetic orders in LaMn3+O3/SrIr4+O3 superlattices. Different from the well-studied Mn4+/Ir4+ superlattices, the Mn3+/Ir4+ structure provides a stronger interfacial effect together with a unique polar discontinuity. An evolution of ferromagnetism is demonstrated and explained by playing with the competition of polar catastrophe and 3d/5d electronic coupling. Furthermore, the symmetry of anisotropic magnetoresistance undergoes a transition from four-fold to two-fold, which is triggered by a gradually enhanced Rashba spin-orbit interaction. This thesis validates that magnetotransport measurements can be used to investigate the unique electrical and magnetic properties. The systematic studies on transition metals and oxides demonstrate the feasibility of revealing emerging phenomena via building transition metal element-based heterostructures. Significantly, these emerging interfacial magnetotransport phenomena enable insights into future spintronic and electronic applications.